Hubungan Modal Sosial dan Perencanaan - Masik, Agustomi (Center for Research and Community Services ITB, 2005)
The metadicipline nature of planning often misleads students relating to what is the focus of this field. Questions arise whether a planner should be focusing on physical aspects or should also dealing with wider concern including social and economic aspe cts. This article explores the meaning of planning, and assess role of social aspect in planning especially social capital concept. It reveals that planning and social capital are reciprocal. Applying interactive and collaborative planning approaches based on communicative rationality increase social capital stock. Conversely, social capital has also importan t roles in planning which are supporting for sustainable development, contextualizing framework, and guid ing the direction of social change, and bridg ing dialogue among disciplines.Keywords: social capital, planning theory, planning